Focus on Faculty: A Missing Link in Community–University Partnerships. Issue 1 (2nd January 2021) - Ng, Jennifer; Martinez, Rebecca S.; Martinez, Sylvia
ABSTRACT: Inherent in the call for this special issue is the idea that Community–University Partnerships (CUPs) matter. In the phrase "community–university partnership, " it is just two entities who are forefronted and assumed to be the primary agents and beneficiaries. Conspicuously absent, however, is recognition of the essential contributions and accompanying career implications for professors who engage Community–University Partnerships (CUPs) as a substantive aspect of their scholarly activities. For many scholars in higher education, their role as consultants bridging the academy and the community is wholly undervalued, and not by the community but by the academy. In this paper, we critically review existing literature about the university professor whose work of envisioning, initiating, developing, and maintaining Community-University Partnerships (CUPs) makes them possible. In particular, we focus on faculty members at traditional research institutions whose merit within the university is determined almost exclusively by their traditional scholarly productivity (i.e., journal publications) and can be diminished by their very engagement in the community. We offer insights into how and why community circumstances and institutional expectations are consequential.